Contribution of Small and Medium-sized Enterprises to Ugandas' GDP - Samuel Lou Mono (Uganda Christian University, 2023)
The purpose of the study was to examine the contribution of small and Medium-sized enterprises to Uganda’s GDP focusing on the Number of SMEs, their tax earnings, employment opportunities created, and revenue generate from their exports. The objectives of the study were to determine the relationship between the number of SMEs and the GDP of Uganda. The second objective was to evaluate the influence of SMEs’ tax contribution on Uganda’s GDP. The third objective was to explore the link between SMEs’ employment generation and Uganda’s GDP. The Last objective was to examine the influence of SMEs’ export earning on Uganda’s GDP The study used a cross sectional and descriptive study design to conduct the study in the whole of Uganda. Secondary data from UBOS was used to describe the contribution of SMEs to Uganda’s GDP. Findings revealed that SMEs has a positive contribution to Uganda’s GDP after studying their number, tax earnings, employment created and their export earnings. This has culminated into the widening of the GDP of Uganda. The study recommends that SMEs need to employ professionals to manage their businesses this will improve on GDP performance since these will establish and strengthen the internal controls as regards financial resources to reduce on mismanagement and misappropriations. Additionally, widening markets and innovation to boost exports and tax earnings should be enhanced by SMEs while Government should provide incentives and infrastructures to SMEs to boost their performance. Lastly, the study is limited to number of SMEs, their tax revenues; employment opportunities created, and export earnings. This is due to resource and time constraint during the study. Researchers can widen their knowledge on SMEs by studying the impact of SMEs growth on the environment, and the challenges faced by SMEs.
This is a dissertation.